Nutritional value of high moisture corn silage in the diet of Holstein cows - Persichetti Júnior, P.; Almeida Júnior, G. a.; Costa, C.; Meirelles, P. r. l.; Silveira, J. p. f.; Panichi, A.; Silva, M. g. b.; Factori, M. A.; Cavasano, F. a.; Mendonça, S. a. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
Five Holstein cows were distributed in a 5x5 latin square design to assess the effect of replacement levels of dry ground corn grain (DGCG) by high moisture corn silage (HMCS) on intake, total nutrient digestibility and plasma glucose, according to the following treatments: 1) 100% DGCG; 2) 75% DGCG and 25% HMCS; 3) 50% DGCG and 50% HMCS; 4) 25% DGCG and 75% HMCS; 5) 100% HMCS. The experiment lasted 70 days, divided into five phases of 14 days each. The digestibility was obtained using chromic oxide (Cr2O3) as the indicator. Fecal samples were collected twice daily and blood samples were collected on the last day of each period before the first meal (0h) and 2h, 4h, 6h and 12h after the meal. There was no effect (P>0.05) on the intake of dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF) and starch. The total apparent digestibility of DM, crude protein (CP), NDF and ADF were not affected (P>0.05) by the treatments, as well as the plasma glucose concentration. However, there was a decreased linear effect (P<0.05) for the protein intake and increased linear effect (P<0.05) for starch digestibility, as the level of HMCS was increased in the diets.

Cinco vacas da raça Holandesa foram distribuídas em quadrado latino 5x5 com o objetivo de se avaliar o efeito de níveis de substituição do grão seco de milho (GSM) pela silagem de grãos úmidos de milho (SGUM) sobre consumo, digestibilidade total dos nutrientes e glicose plasmática, o que constituiu os tratamentos: 1) 100% GSM; 2) 75% GSM e 25% SGUM; 3) 50% GSM e 50% SGUM; 4) 25% GSM e 75% SGUM; 5) 100% SGUM. O período experimental durou 70 dias, divididos em cinco fases de 14 dias. A digestibilidade foi obtida utilizando-se óxido crômico (Cr2O3) como indicador. Foram colhidas amostras fecais duas vezes por dia, bem como amostras de sangue no último dia dos períodos, antes da primeira refeição (zero hora), duas, quatro, seis e 12 horas após a refeição. Não houve efeito (P>0,05) sobre o consumo de matéria seca (MS), fibra em detergente neutro (FDN), fibra em detergente ácido (FDA) e amido. A digestibilidade aparente total da MS, a proteína bruta (PB), a FDN e a FDA não foram afetadas (P>0,05), assim como a concentração de glicose plasmática. Houve efeito linear decrescente (P<0,05) para consumo de PB e linear crescente (P<0,05) para digestibilidade do amido, à medida que se aumentou a inclusão de SGUM.
Valor nutritivo da silagem de grãos úmidos de milho na alimentação de vacas da raça Holandesa
Keywords: amido; digestibilidade; glicose; óxido crômico; processamento; starch; digestibility; glucose; chromium oxide; processing